Evaluation of thin mercury film rotating disk electrode to perform absence of gradients and Nernstian equilibrium stripping (AGNES) measurements - Rocha, L. S. (2013)
In the present work, the applicability of thin mercury film on a rotating disk electrode (TMF-RDE), to assess the free metal ion concentration by the absence of gradients and Nernstian equilibrium stripping (AGNES), is evaluated. The thickness of the mercury film and several AGNES parameters has been optimized. A nominal 16 nm film is chosen due to the higher signal (faradaic current) relative to the value of the noise (capacitive current). Due to the smaller volume to area ratio, the deposition time needed to reach a certain preconcentration factor (Y) is much shorter than in larger electrodes, like the HMDE. The limit of detection (3σ) for lead(II) is 7.4 × 10−9 M and 7.2 × 10−8 M for a Y of 5000 (deposition time of 150 s) and 1000 (deposition time of 100 s), respectively. A specific mathematical treatment is developed in order to subtract a corrected blank taking into account the degradation of the thin film (presumably, falling down of drops). The couple TMF-RDE/AGNES is successfully applied for speciation purposes in the systems Pb(II)–latex nanospheres and Pb(II)–IDA (iminodiacetic acid), where the stability constants calculated for both systems agree with values reported in the literature.